Experimental researches of the technology of restoration of the bottom surface of reinforced concrete structures with the use of formwork - Molodid, O.; Sharikina, N. (Ways to Improve Construction Efficiency, 2018)
The authors present a methodology for performing experimental research, which involves the artificial destruction of reinforced concrete beams and their gradual restoration with further study of physical and mechanical parameters. The restoration of the lower surface of beams was carried out by high-flowing concrete mixtures, which formed in formwork structures. Experimental studies were carried out over the restored beams, which resulted in the bending strength of the reinforced beams increased by 2.5 times compared with the control beams. The studies to determine the strength of the adhesion of recovered fragments with the base have established that for both types of soluble mixtures, which are used in the restoration of beams, it is practically the same and is 0.8 MPa.